The global proliferation of aquatic, benthic Microcoleus: Taxonomy, distribution, toxin production, ecology, and future directions - Laura T. Kelly; Daniel G. Beach; Joanna R. Blaszczak; Keith Bouma-Gregson; Sydney M. Brown; Haowu Cheng; Janette L. Davidson; Jutta Fastner; Marcus Francis; Andrea Garcia Jimenez; Laurel Genzoli; Ramesh Goel; et al. (Water Research, 2026)

Cyanotoxins associated with macrophytes in Berlin (Germany) water bodies – Occurrence and risk assessment - Jutta Fastner; Jonna Teikari; Anja Hoffmann; Antje Köhler; Sebastian Hoppe; Elke Dittmann; Martin Welker (Science of The Total Environment, 2023)

Decades needed for ecosystem components to respond to a sharp and drastic phosphorus load reduction - Ingrid Chorus; Antje Köhler; Camilla Beulker; Jutta Fastner; Klaus van de Weyer; Tilo Hegewald; Michael Hupfer (Hydrobiologia, 2020)
Lake Tegel is an extreme case of restoration: inflow treatment reduced its main external phosphorus (TP) load 40-fold, sharply focused in time, and low-P water flushed the lake volume ≈ 4 times per year. We analysed 35 years of data for the time TP concentrations took to decline from ≈ 700 to 20–30 µg/l, biota to respond and cyanobacteria to become negligible. The internal load proved of minor relevance. After 10 years, TP reached 35–40 µg/l, phytoplankton biomass abruptly declined by 50% and cyanobacteria no longer dominated; yet 10 years later at TP < 20–30 µg/l they were below quantifiable levels. 20–25 years after load reduction, the lake was stably mesotrophic, macrophytes had returned down to 6–8 m, and vivianite now forms, binding P insolubly in the sediment. Bottom-up control of phytoplankton through TP proved decisive. Five intermittent years with a higher external P load caused some ‘re-eutrophication’, delaying recovery by 5 years. While some restoration responses required undercutting thresholds, particularly that of phytoplankton biomass to TP, resilience and hysteresis proved irrelevant. Future research needs to focus on the littoral zone, and for predicting time spans for recovery more generally, meta-analyses should address P load reduction in combination with flushing rates.

Erratum to: Cyanobacterial blooms. Ecology, prevention, mitigation and control: Editorial to a CYANOCOST Special Issue - Bastiaan W. Ibelings; Jutta Fastner; Myriam Bormans; Petra M. Visser (Aquatic Ecology, 2016)

Cyanobacterial blooms. Ecology, prevention, mitigation and control: Editorial to a CYANOCOST Special Issue - Bastiaan W. Ibelings; Jutta Fastner; Myriam Bormans; Petra M. Visser (Aquatic Ecology, 2016)

CYANOCOST special issue on cyanobacterial blooms: synopsis—a critical review of the management options for their prevention, control and mitigation - Bastiaan W. Ibelings; Myriam Bormans; Jutta Fastner; Petra M. Visser (Aquatic Ecology, 2016)

Combating cyanobacterial proliferation by avoiding or treating inflows with high P load—experiences from eight case studies - Jutta Fastner; Sally Abella; Arni Litt; Giuseppe Morabito; Lajos Vörös; Károly Pálffy; Dietmar Straile; Reiner Kümmerlin; David Matthews; M. Geoff Phillips; Ingrid Chorus (Aquatic Ecology, 2016)

Microcystin production revisited: conjugate formation makes a major contribution - Sven Meissner; Jutta Fastner; Elke Dittmann (Environmental Microbiology, 2013)
Summary The impact of environmental stimuli on the production of the widespread cyanobacterial hepatotoxin microcystin ( MC ) is under debate. Whereas transcriptional studies of the biosynthetic genes suggest a clear influence of light conditions on toxin production the data for the metabolite itself are inconsistent and highly strain‐specific. Here, we have reassessed the MC content by using two immunological detection techniques that allow a parallel quantification of MC in the methanolic extracts and the residual pellet fraction that contains high molecular weight proteins. Our results show a significant proportion of MC in the protein bound fraction in strains of M icrocystis and P lanktothrix and of the related toxin nodularin ( NOD ) in N odularia . Moreover, we could show a very strong increase of MC after high light illumination in the protein fraction contributing to a significant overall increase in MC production under these conditions that is not seen in extracts analysed by LC‐MS and ELISA . The fact that a considerable portion of MC is neglected with current analysis techniques was also confirmed for selected field samples. Immunofluorescence studies suggest strain‐specific differences in the amount of MC conjugate formation.

Detection of Planktothrix rubescens (Cyanobacteria) associated with microcystin production in a freshwater reservoir - Sérgio Paulino; Elisabete Valério; Natália Faria; Jutta Fastner; Martin Welker; Rogério Tenreiro; Paulo Pereira (Hydrobiologia, 2009)

Diversity of Microcystis aeruginosa isolates (Chroococcales, Cyanobacteria) from East-African water bodies - Sigrid Haande; Andreas Ballot; Thomas Rohrlack; Jutta Fastner; Claudia Wiedner; Bente Edvardsen (Archives of Microbiology, 2007)

Abundance of active and inactive microcystin genotypes in populations of the toxic cyanobacterium Planktothrix spp. - Rainer Kurmayer; Guntram Christiansen; Jutta Fastner; Thomas Börner (Environmental Microbiology, 2004)
Summary To investigate the abundance of active and inactive microcystin genotypes in populations of the filamentous cyanobacterium Planktothrix spp., individual filaments were grown as clonal strains in the laboratory and analysed for microcystin synthetase ( mcy ) genes and microcystin. Twenty‐three green‐pigmented strains of P. agardhii originating mostly from shallow water bodies fell into two groups, those possessing mcyA and those lacking mcyA. In contrast, all of the 49 strains that were assigned to the red‐pigmented P. rubescens contained mcyA . One strain of P. agardhii and eight strains of P. rubescens contained the total microcystin synthetase gene cluster but were found inactive in microcystin synthesis. To investigate the natural abundance of inactive mcy genotypes in P. rubescens individual filaments sampled from Lake Irrsee and Lake Mondsee (Austria) were analysed directly for the presence of mcyA and microcystin by matrix‐assisted laser desorption/ionisation time‐of‐flight mass spectrometry. All filaments assigned to P. rubescens contained mcyA . The proportion of inactive microcystin genotypes in populations with a low (Irrsee) or high density (Mondsee) of P. rubescens was 5% and 21%, each. The results of this study demonstrate that P. rubescens typically contain mcy genes whereas P. agardhii have a patchy distribution of mcy genes. In both species microcystin producers co‐occur with non‐microcystin producers due to the absence/inactivation of mcy genes.

First Report of a Microcystin-Containing Bloom of the Cyanobacteria Microcystis spp. in Lake Oubeira, Eastern Algeria - Aïcha-Beya Nasri; Noureddine Bouaïcha; Jutta Fastner (Archives of Environmental Contamination and Toxicology, 2004)

Isolation, Characterization, and Quantitative Analysis of Microviridin J, a New Microcystis Metabolite Toxic to Daphnia - Thomas Rohrlack; Kirsten Christoffersen; Poul Erik Hansen; Wei Zhang; Olaf Czarnecki; Manfred Henning; Jutta Fastner; Marcel Erhard; Brett A. Neilan; Melanie Kaebernick (Journal of Chemical Ecology, 2003)